FRACIONAMENTO QUÍMICO DA MATÉRIA ORGÂNICA DO SOLO EM SISTEMAS DE MANEJO E USO DO SOLO - PAULINO, Leonardo Albino; AGUIAR, Franciele Kelle Oliveira Moura; LIMA, Isabela Machado de Oliveira; ENSINAS, Simone Cândido; MARQUES FILHO, Wolff Camargo; BARBOSA, Giselle Feliciani (ANAIS DO ENIC, 2018)
-